Brain Switch for Reflex Micturition Control Detected by fMRI in Rats - Tai, Changfeng (American Physiological Society, 2009)
The functions of the lower urinary tract are controlled by complex pathways in the brain that act like switching circuits to voluntarily or reflexly shift the activity of various pelvic organs (bladder, urethra, urethral sphincter, and pelvic floor muscles) from urine storage to micturition. In this study, functional magnetic resonance imaging (fMRI) was used to visualize the brain switching circuits controlling reflex micturition in anesthetized rats. The fMRI images confirmed the hypothesis based on previous neuroanatomical and neurophysiological studies that the brain stem switch for reflex micturition control involves both the periaqueductal gray (PAG) and the pontine micturition center (PMC). During storage, the PAG was activated by afferent input from the urinary bladder while the PMC was inactive. When bladder volume increased to the micturition threshold, the switch from storage to micturition was associated with PMC activation and enhanced PAG activity. A complex brain network that may regulate the brain stem micturition switch and control storage and voiding was also identified. Storage was accompanied by activation of the motor cortex, somatosensory cortex, cingulate cortex, retrosplenial cortex, thalamus, putamen, insula, and septal nucleus. On the other hand, micturition was associated with: 1) increased activity of the motor cortex, thalamus, and putamen; 2) a shift in the locus of activity in the cingulate and insula; and 3) the emergence of activity in the hypothalamus, substantia nigra, globus pallidus, hippocampus, and inferior colliculus. Understanding brain control of reflex micturition is important for elucidating the mechanisms underlying neurogenic bladder dysfunctions including frequency, urgency, and incontinence.